2017
DOI: 10.1136/bjsports-2016-097372.204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Perturbation on Neuromuscular Trunk Activation Pattern During Core-Specific Sensorimotor Exercise

Abstract: BackgroundSensorimotor exercises (SE) are evident to enhance neuromuscular activity of the trunk muscles (TM). However, it is unclear if an additional unexpected perturbation leads to higher muscular activity and therefore enhances training efficacy.ObjectiveTo analyse effects of additional unexpected perturbations on trunk neuromuscular activation pattern during SE.DesignCross-sectional design.SettingUniversity Outpatient Clinic, Sports Medicine Centre.ParticipantsTen healthy, normal active participants (5 m/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, additive sensorimotor perturbation will be applied to one (control group) and all exercises (all intervention groups) to enhance the efficacy of neuromuscular activity while exercising [ 24 26 ]. In a pilot study, Mueller et al [ 25 ] showed that the use of additional perturbations during core-specific sensorimotor exercises was superior for enhancing trunk neuromuscular activity. Higher EMG amplitudes might indicate higher exercise intensity, but additional functional benefits and long-term effects still need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additive sensorimotor perturbation will be applied to one (control group) and all exercises (all intervention groups) to enhance the efficacy of neuromuscular activity while exercising [ 24 26 ]. In a pilot study, Mueller et al [ 25 ] showed that the use of additional perturbations during core-specific sensorimotor exercises was superior for enhancing trunk neuromuscular activity. Higher EMG amplitudes might indicate higher exercise intensity, but additional functional benefits and long-term effects still need to be investigated.…”
Section: Discussionmentioning
confidence: 99%